Synergist interaction between angiotensin II and DOCA on sodium and water balance in rats - Camargo, Luiz Antonio de Arruda [UNESP]; Saad, Wilson Abrão [UNESP]; Luca Junior, Laurival Antonio de [UNESP]; Renzi, Antonio [UNESP]; Silveira, José Eduardo Nogueira [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 1994)
Blockade of central angiotensin receptors with the specific antagonist [Leu8]-ANG II abolished water ingestion and water and sodium excretion induced by infusion of angiotensin II (ANGII) into the lateral ventricle (LV) of rats. The antagonist reduced but did not suppress the salt appetite induced by ANGII infusion. Subcutaneous injection of deoxycorticosterone acetate (DOCA) caused increases in water and 3% NaCl ingestion and decreases in sodium excretion. When central ANGII infusion was combined with peripheral DOCA, the water intake was similar to that induced by ANGII alone and the ingestion of 3% NaCl was increased, whereas sodium excretion was inhibited. When ANGII was infused alone, a detailed temporal analysis of fluid and sodium balance showed a negative balance similar those saline controls that persisted throughout the experiment. Combined administration of ANGII and DOCA induce significant changes in water and sodium balance. Sodium and water maintained a positive balance through out the 8-h experiment. The data support an interaction of central ANGII and DOCA on sodium intake and water and sodium balance. © 1994.
Keywords: Angiotensin II; DOCA; Salt ingestion; Sodium excretion; Urine excretion; Water ingestion; Angiotensin; Angiotensin 2 receptor antagonist; Deoxycorticosterone acetate; Animal experiment; Controlled study; Fluid balance; Fluid intake; Intracerebroventricular drug administration; Male; Natriuresis; Nonhuman; Priority journal; Rat; Salt intake; Subcutaneous drug administration; Animal; Desoxycorticosterone; Homeostasis; Male; Natriuresis; Rats; Support, Non-U.S. Gov't; Water-Electrolyte Balance